IMAM BUKHARI - Murodkhonov Mukhammad Sodiq (Scholar Express Journal, 2022)
Imam al-Bukhari's Al-Jami 'as-Sahih is the main source after the Qur'an according to Islamic teachings. The full text of this work is "Al-Jami 'as-sahih al-musnad min hadith's Rasulullah-sallallahu alayh'i wa sall'am wa sunanih'i wa ayyamih'i" or, as the historian Badruddin al-Aini writes, "Al-Jami' almusnad al-sahih al-mukhtasar min umuri Rasulullah-sallallaahu alayh'i wa sall'am wa sunanih'i wa ayyamih'i ”is abbreviated as It is known as-Sahih alBukhari. This article discusses Imam al-Bukhari.
Keywords: Imam al-Bukhari; Al-Jame 'as-Sahih; hadith's, work; scholar